The Role of English Proficiency in Enhancing Tourism Service Quality in Bali (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2026)
This study examined the indispensable role of English in tourism services through a case study conducted in Bali, one of Indonesia’s primary international tourist destinations. The problem addressed in this research concerned the extent to which English proficiency influenced service quality and visitor satisfaction in tourism-related sectors. A qualitative approach was employed, involving observations, in-depth interviews with tourism workers, and document analysis across hospitality, transportation, and local attraction services. The findings indicated that English functioned not only as a communication tool but also as a bridge for cultural exchange, enabling service providers to respond accurately to tourists’ needs and expectations. Limited English proficiency was found to hinder effective interaction, often leading to misunderstandings and reduced service efficiency. Conversely, workers with stronger English skills demonstrated greater confidence, adaptability, and professionalism, which contributed to higher levels of tourist satisfaction. The study concluded that English competency played a central role in sustaining service excellence and competitiveness in Bali’s tourism industry. Strengthening language training programs for tourism practitioners was therefore identified as a practical solution to improve service quality and maintain Bali’s reputation as a global destination.